Second Life as a Virtual Playground for Language Education A Practical Guide for Teaching and Research - Chen, Julian (Taylor & Francis, 2022)
This insightful book offers language teachers and teachers in training the opportunity to delve into 3D virtual worlds and see the benefits they provide for effective language teaching.